Role of 3D CT in Diagnosis of Skull Base Fractures - Michelle W. Mandang; Eko Prasetyo; Stephanus J. Ch. Tangel (Universitas Sam Ratulangi, 2022)
Abstract: Traumatic brain injury (TBI) including skull base fracture is one of the most common medical encounters and the leading cause of disability and death. The gold standard examination for skull base fracture is computerized tomography (CT scan). Since skull base has irregular anatomy and thin bony plates, CT 3 dimension (3D CT) is needed to detect this fracture rapidly and accurately compared to conventional CT scan. Â This study aimed to evaluate the use of 3D CT in the diagnosis of skull base fractures. This was a literature review study using databases of ClinicalKey, Google Scholar, and PubMed. The keywords were three-dimensional computed tomography (CT 3D) and skull base fractures. The results obtained 15 articles related to this topic. The 3D CT could detect skull base fractures more rapidly and accurately than other examinations such as X-ray, 2D CT, solid (SVR) and transparent (TVR) volume-rendering technique, and maximum intensity projection (MIP). In conclusion, 3D CT plays an important role in the diagnosis of skull base fractures.Keywords: 3D CT; skull base fractures; traumatic brain injuryÂ Abstrak: Cedera kepala akibat trauma merupakan salah satu penyebab utama kecacatan dan kematian. Patah tulang dasar kepala sering terjadi pada cedera kepala akibat trauma. Pemeriksaan baku emas untuk patah tulang dasar kepala menggunakan modalitas Computerized Tomography (CT scan). Dasar kepala memiliki anatomi yang tidak beraturan dan ketebalan tulang yang tipis, sehingga penggunaan CT 3 dimensi (CT 3D) dibutuhkan untuk mendeteksi patah tulang secara cepat dan akurat dibandingkan CT scan konvensional. Penelitian ini bertujuan untuk mengulas bahan pustaka dengan topik penggunaan CT 3D pada diagnosis patah tulang dasar kepala. Jenis penelitian ialahÂ suatu literature review. Hasil penelitian mendapatkan 15 jurnal yang berhubungan dengan topik ini. CT 3D dapat mendeteksi fraktur dasar kepala dengan lebih cepat dan akurat dibandingkan pemeriksaan lainnya, seperti X-ray, 2D CT, solid (SVR) and transparent (TVR) volume-rendering technique, dan maximum intensity projection (MIP). Simpulan penelitian ini ialah CT 3D berperan penting pada diagnosis patah tulang dasar kepala.Kata kunci: CT 3D; patah tulang dasar kepala; cedera kepala akibat trauma